Sustainability assessments of commercial urban agriculture – a scoping review - Milestad, Rebecka; de Jong, Annelise; Bustamante, Maria J.; Molin, Elvira; Martin, Michael; Malone Friedman, Carrie (Frontiers in Sustainable Food Systems, 2024)
The field of urban agriculture has seen an increase in development and attention in recent years, with a large share of literature addressing whether urban agriculture may pose a solution for food insecurity and combat environmental impacts. However, few studies have examined the many sustainability claims of urban agriculture systems, especially for urban farms intended for larger output and commercial ends. In this study, we analyze sustainability assessments of urban agriculture for commercial implementation. We do this by exploring the methods employed for conducting sustainability analyses, outlining the different urban agriculture cultivation systems, analyzing which sustainability aspects are considered, looking into what the sustainability analyses conclude, and studying how authors anticipate the knowledge gained from their sustainability assessments can be used. Environmental aspects of sustainability were more often assessed than other sustainability aspects, and LCA research practice was used for the majority of environmental assessments. Some studies compared the environmental benefits of different types of urban agriculture systems, but this was not conclusive overall as to what systems would be more environmentally beneficial. This suggests that urban agriculture’s sustainability cannot be universally categorized but should be assessed in relation to specific environmental conditions and urban contexts. Future research should aim to develop more nuanced frameworks for evaluating the environmental, social, economic and governance impacts of urban agriculture.